"The narrative methods in The Lettar Of Asahel wa ashahij" - عيسى حكمت; نمر مصطفى; علي فاطمة (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The narrative style is considered an important factor in the construction of the story. It indicates to reaching the narrator’s point of view to the recipient. The term narrative style overlaps with the term narrative vision, which means the point of view, or the position the narrator takes from the surrounding world. This paper deals with the narrative methods on which the narrator relied on in " Risalat Asahel wa ashahij" : Which is Panoramic style, Dialogue style, and Informative style. Each style relates in its location to the character and extent of viewing the events. The Panoramic and Informative styles overlap with the (vision from behind), whereas the Dialogue style overlaps with the (vision with), it is worth noting: The narrative styles used in any fictional work reveals an integrated vision of it and make it easier for the recipient to understand and realize its meanings and dimensions.